Socioecological risk factors associated with teen pregnancy or birth for young men: A scoping review. (July 2019) - Fasula, Amy M.; Chia, Victoria; Murray, Colleen Crittenden; Brittain, Anna; Tevendale, Heather; Koumans, Emilia H.
Abstract: Introduction: Teen pregnancy prevention typically focuses on young women, overlooking the unique prevention needs of young men. Identifying factors associated with teen pregnancy for young men is essential to developing relevant and effective programming. Methods: We conducted a scoping review of studies with findings on factors associated with pregnancies/birth specific to young men. We searched Scopus, OVID, and PubMed databases for peer-reviewed articles published from 2000 to 2015. We reviewed 1750 articles for inclusion of studies conducted in the United States with a sample size greater than 200 that assessed the effect of factors on teen pregnancy/birth using multivariate, male-specific analyses. Two coders abstracted 48 articles (having established 80% reliability with 10% of the articles). We grouped study variables into factors and used a matrix to summarize findings for each factor. During analysis, 29 articles were excluded for a final sample of 19 articles, each describing a separate study. Results: Study settings included households, healthcare organizations, schools, neighborhoods, and correctional facilities. Factors showing associations with teen pregnancy/birth included: experiencing childhood abuse; engaging in serious or repeated delinquent behaviors; substance abuse; having a teen parent; serious family disruption; not living with either parent; and Hispanic ethnicity. No studies assessed knowledge and attitudes about contraceptive methods, or access and use of clinical services; and few assessed relationship factors (n = 4) or gender and power (n = 1). Conclusions: Factors related to disadvantaged social contexts were associated with teen pregnancy/birth. Resilience-based research may identify protective factors to support vulnerable families and youth.